Literary Check on Women's Maternity (Journal of Parents and Teachers, 2025)
The article discusses a series of roundtable discussions addressing topics such as feminism, the world, culture, motherhood, idealism, and even realism, where dialogue is the key to achieving understanding.
Keywords: round tables; feminism; culture; world; realism